Thinking on your feet: Beauty and auto small businesses maneuver the risks of the COVID-19 pandemic - Moreno Ramírez, Denise; Gutenkunst, Shannon; Honan, Jenna; Ingram, Maia; Quijada, Carolina; Chaires, Marvin; Sneed, Sam J.; Sandoval, Flor; Spitz, Rachel; Carvajal, Scott; Billheimer, Dean; Wolf, Ann Marie; et al. (Frontiers in Public Health, 2022)
On March 11, 2020, the World Health Organization officially declared SARS-CoV-2 a pandemic, and governments and health institutions enacted various public health measures to decrease its transmission rate. The COVID-19 pandemic made occupational health disparities for small businesses more visible and created an unprecedented financial burden, particularly for those located in communities of color. In part, communities of color experienced disproportionate mortality and morbidity rates from COVID-19 due to their increased exposure. The COVID-19 pandemic has prompted the public to reflect on risks daily. Risk perception is a critical factor influencing how risk gets communicated and perceived by individuals, groups, and communities. This study explores competing risk perceptions regarding COVID-19, economic impacts, vaccination, and disinfectant exposures of workers at beauty salons and auto shops in Tucson, Arizona, using a perceived risk score measured on a scale of 1–10, with higher scores indicating more perceived risk. The primary differences between respondents at beauty salons and auto shops regarding their perceived risks of COVID-19 vaccination were between the vaccinated and unvaccinated. For every group except the unvaccinated, the perceived risk score of getting the COVID-19 vaccine was low, and the score of not getting the COVID-19 vaccine was high. Study participants in different demographic groups ranked economic risk the highest compared to the other five categories: getting the COVID-19 vaccine, not getting the COVID-19 vaccine, COVID-19, disinfection, and general. A meaningful increase of four points in the perceived risk score of not getting the COVID-19 vaccine was associated with a 227% (95% CI: 27%, 740%) increase in the odds of being vaccinated. Analyzing these data collected during the coronavirus pandemic may provide insight into how to promote the health-protective behavior of high-risk workers and employers in the service sector during times of new novel threats (such as a future pandemic or crisis) and how they process competing risks.